2020
DOI: 10.1680/jgein.20.00017
|View full text |Cite
|
Sign up to set email alerts
|

Encased stone columns: coupled continuum – discrete modelling and observations

Abstract: The present research focuses on the simulation of encased stone columns in a 2D state by utilising the coupled finite difference method (FDM) and discrete element method (DEM). The stone column material was modelled by DEM using irregularly shaped particles, and the geotextile used as the encasement of the stone column was simulated using parallel-bonded particles. The surrounding clayey soil was modelled by FDM. Two models were combined by employing a direct coupling method. After validating the coupled DEM-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The encasement works well in an embankment of soft clayey soil; there is also a reduction in hoop tension [25][26][27]. By reinforcing the entire column, it improves the magnitude of loadcarrying capacity of the column [28]; where the optimum length for encasement is four times the diameter of the column [29]. While considering the stress factor, it is observed that the resultant stress on the column top reduces by 65% when the diameter increases [30].…”
Section: Introductionmentioning
confidence: 97%
“…The encasement works well in an embankment of soft clayey soil; there is also a reduction in hoop tension [25][26][27]. By reinforcing the entire column, it improves the magnitude of loadcarrying capacity of the column [28]; where the optimum length for encasement is four times the diameter of the column [29]. While considering the stress factor, it is observed that the resultant stress on the column top reduces by 65% when the diameter increases [30].…”
Section: Introductionmentioning
confidence: 97%